Education And Training Management In Improving The Performance Of Kartika Cooperative Employees - Maulana, Arman; Priyatna, Soeganda; Saeful Insan, Husen; Helmawati, Helmawati (CV. Inara, 2021)
PeThis study aims to determine the management of education and training in improving the performance of the Kartika Cooperative. Education and training management includes education and training planning, training organization, training implementation, training evaluation, training constraints and solutions. This research is a descriptive qualitative research using purpose sampling technique to determine the subject of this research. The object of research is the chairman of the cooperative, the secretary of the treasurer, employees, and members of the cooperative. Data collection techniques used are interviews, observation and documentation. Descriptive qualitative analysis of the data obtained. Checking the validity of the data is done by triangulation of sources and methods.The results showed that the management of Kartika Cooperative education and training includes: 1) Training planning, including planning the location and management of the training according to the project and the number of participants, preparing the schedule according to the training project, media and methods. coordinate with each other to adjust the material, and plan the material according to the theme, and determine the speaker based on the quality and experience of the instructor, 2) The implementation of the training begins with the manager's direction, attendance, and the opening of the training. At the beginning of the training, management briefing, attendance, and opening of the training. The chairman of the cooperative management gave a speech and at the same time opened the training. Participants' input material is combined with themes, methods, presenters, and use of space, and is managed by the education and training manager. The implementation of the training ended with an evaluation process carried out by participants by filling out a questionnaire. Finally, it ends with the submission of a training certificate. However, the use of space is not in accordance with the ideal conditions of each participant, namely 4 square meters, the training schedule is not in accordance with the original plan, and the number of managers is not proportional to the number of participants, 3) Evaluation of the training process, to determine the criteria, tools and forms of the results of the training evaluation . The evaluation criteria include the delivery of material, the attitude of the presenters, the neatness of data provision, the method of the speaker, the motivation of the participants, the service manager, and the level of potential of the participants, the style, attitude, behavior, and language of the speaker. While the training evaluation tool is in the form of a questionnaire, and the results of the evaluation are training reports, questionnaires, and statistical data processing results. Evaluation of the results of the training, employees who initially only did the work without knowing in detail the meaning of the work being done, but with the training, employees better understand the systematic system. 4) Education and training constraints, the material is not in accordance with the needs of the training and the less than optimal preparation of the environment for the transfer of post-training knowledge but at work often applies work habits from experience, 5) Training solutions.